The impact of maternal nutrition on the offspring - Hornstra, G.Th; Uauy, Ricardo; Yang, Xiaoguang (Karger, 2005)
A collection of papers presented at a workshop that focused on nutrition in pregnancy and its consequences for the development of the fetus. Intended for professional public.
Nestlé Nutrition workshop series. Paediatric programme, ISSN 0742-2806 volume 55
Keywords: Fetal Diseases; Fetal Development; vývoj plodu; embryologie a teratologie; nemoci plodu; nutriční terapie, dietoterapie a výživa; Developmental Disabilities; Child Development; Maternal Nutritional Physiological Phenomena; perinatologie a neonatologie; fyziologie výživy v mateřství; vývojové poruchy u dětí; vývoj dítěte; Pregnancy Complications; komplikace těhotenství